Monadic curry algebras Q tau - Abe, Jair Minoro [UNESP]; Akama, Seiki; Nakamatsu, Kazumi; Apolloni, B.; Howlett, R. J.; Jain, L. (Springer, 2007)
In this paper we present an algebraic version of the annotated predicate logics Q tau [1] by using the concept of Curry Algebras [5]. The algebraic structure obtained is called Curry Algebras Q tau. We study some basic properties of these algebras. The main ideas involved lean heavily on the works by P. Halmos and N.C.A. Da Costa [9], [5].
Keywords: curry algebras; monadic algebras; paraconsistent annotated logic; algebraic logic